Crucial Factors that Affect Shortage of Skilled Workers for Construction Projects - Agalawatta, T (NSBM Green University, 2018)
This research paper defines the most crucial factors affecting to skilled worker shortage and ways to overcome from this issue with their significance outcome. Construction projects are frequently subject to problem of skilled worker shortage, which constrains project execution. Since construction is a worker intensive industry, the shortage of worker has become the crucial risks that hindering the construction project in achieving its success. However, by conducting this research the researcher may address the specific objectives of this research as well which basically finds the relationship of crucial factors with the skilled worker shortage. However, in order to conduct this research on this topic the researcher may analyse the existing knowledge on this skilled worker shortage.
Keywords: construction; skilled worker; crucial; shortage; significance; construction projects; salary scale; worker migration